Decreased cathepsin V expression due to Fli1 deficiency contributes to the development of dermal fibrosis and proliferative vasculopathy in systemic sclerosis - Noda, S.; Asano, Y.; Takahashi, T.; Akamata, K.; Aozasa, N.; Taniguchi, T.; Ichimura, Y.; Toyama, T.; Sumida, H.; Kuwano, Y.; Yanaba, K.; Tada, Y.; et al. (Rheumatology (Oxford, England), 2013)
Cathepsin V (CTSV) is a proteolytic enzyme potentially modulating angiogenic processes, collagen degradation and keratinocyte differentiation. We aimed to investigate the clinical association of serum CTSV levels and the mechanism by which CTSV expression is altered in SSc. Serum CTSV levels were determined by ELISA in 51 SSc and 18 healthy subjects. CTSV expression was evaluated by immunostaining in SSc and normal skin and by RT-real-time PCR in normal and SSc dermal fibroblasts, normal dermal fibroblasts treated with TGF-β1 or Fli1 siRNA and human dermal microvascular endothelial cells (ECs) treated with Fli1 siRNA. Serum CTSV levels were significantly lower in dcSSc and lcSSc patients than in healthy controls. In early-stage dcSSc, serum CTSV levels were remarkably and uniformly decreased compared with healthy controls. The decrease in serum CTSV levels in mid- and late-stage dcSSc and in lcSSc was linked to the development of proliferative vasculopathy. CTSV expression was decreased in microvascular ECs, pericytes/vascular smooth muscle cells and keratinocytes of dcSSc and lcSSc skin and in dermal fibroblasts of dcSSc skin compared with control skin. Consistently, CTSV expression was decreased in cultured dermal fibroblasts from early-stage dcSSc. Furthermore, mRNA levels of the CTSV gene were significantly decreased in normal fibroblasts treated with TGF-β1 or Fli1 siRNA and in human dermal microvascular ECs treated with Fli1 siRNA. Loss of CTSV expression may contribute to the development of fibrosis, vasculopathy and the altered phenotype of keratinocytes in SSc.